Diffraction of light on one and two infinitly narrow slits in a screen - Bezugliy, A.V. (Radiotekhnika, 2025)
The work addresses the solution of the problems of light diffraction at one and two narrow slits in an opaque screen. The diffraction patterns were analyzed. It was established that their appearance depends on the ratio of the characteristic size of the obstacle to the wavelength of the photon. When this ratio is less than unity, we have a smoothly changing illumination with a maximum at the center of symmetry of the system. If it one is greater than unity, then the pattern has the appearance of light and dark stripes. The numerical value of the specified ratio determines the number of maxima. The obtained results allow us to assume that the reason for the well-known paradox in the interpretation of experiments on the diffraction of light at one and two narrow slits is thе next. The experiments at one slit was carried out for the case when the wavelength was greater than the width of the slit, and at two slits - for the case, when the wavelength is much smaller than the distance between slits.